Approach to making strategies for network security enhancement based on attack graphs - SI Jia-quan1; ZHANG Bing2; MAN Da-peng1; YANG Wu1 (Tongxin xuebao)
In order to improve the overall security of networks,a method of making strategies for the network security enhancement based on global attack graphs was proposed.The method calculated the probability of the network states transition by using global attack graphs.On this basis,the security loss of network states and the criticality of security elements were gotten.Finally,security elements were deleted based on maximum criticality first.The analysis of the ex-ample indicates that the enhancement strategies made by the method can improve the overall security of networks,and the operability is better than traditional methods.